Interação entre a infecção natural por Eimeria bateri E aflatoxicose induzida em codornas japonesas (Coturnix japonica) - Cardozo, Sergian Vianna (2010)
Eimeriosis is a major parasitic disease in poultry, causing severe economic losses, mainly due to episodes of diarrhea and deaths in young animals. This work aimed to study the macroscopic and microscopic changes in Japanese quails with natural infection for Eimeria bateri and defied with aflatoxin beyond following the dynamics of shedding the oocysts throughout the development of the infection, front to the effect caused due to the intoxication of aflatoxin in Japanese quails. A total of 80 birds were used in this experiment and they were divided randomly in four experimental groups and 20 birds per group. The animals of groups I and III were infected with E. bateri oocysts, quails in groups II and III were intoxicated with aflatoxin in the 0.04 dose of mg/kg of body weight and group IV (control) was constituted by free animals of infection by coccidia and intoxicationf of aflatoxin. In days 6, 11, 18 and 25 after intoxication, 20 birds were eutanasied and posted for time, being five of each experimental group. The weights of the referring organs as gizzard, cloacal bursa, liver, and heart of each eutanazied birds, were listed and express as percentage of corporal weight of each bird when they were removed.The oocysts shed by quails were isolated and were identified by using a modified Sheater centrifugal-flotation technique. After analysis of the morphoometric data and the evaluation of the dynamics of shedding E. bateri oocysts, macrocospic changes and microscopical alterations were observed in the birds organs. Only E. bateri was found and identified parasitized quails of groups I and III, being which oocysts shed by birds of the group III had small morphologic changes in its structure. Gross changes were observed in the liver of animals in groups II and III that had a yellow color and crispy texture when compared to the control group. The heart was observed an increase in organ size in birds of group II. After histhological procedure were observed microscopic changes mainly in the liver and small intestine. In the mucosal cells endogenous forms as gamonts and macrogametocytes of E. bateri were observed. Histopathological changes were observed in the liver of quails intoxicated with aflatoxin only and it was observed mainly in quails posted at the first time (60 DAI) in the II group. The main lesion was consisted of intracytiplasmatic macrovacuolization of the hepatocytes, sinusoidal congestion of the central lobular vains and vessels of the portal spaces with discret inflammatory infiltration, followed by diffuse periportal necrosis. In the heart, microscopic lesions were associated to experimental intoxication and were characterized by intracellular and interstitial edema. After analysis of the alive and carcass body weight and the relative weight of visceras of the quails in the different necropsy days were observed by having significant changes in the alive and carcass weights as well as in the relative liver and heart weights of the experimental groups. In addition to the pathological effects of aflatoxin in the guts of birds, it was found that this toxin interferes with the dynamics of elimination and the morphology of the oocysts of E. bateri.